Comparison of Indicators of Risk of Deafness in Newborns Studied in the Years 1995 and 2005 - Lopes, Monique Kelly Duarte; Santos, Teresa Maria Momensohn (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: The data submitted by the Center of Epidemiological Surveillance of the State of São Paulo indicates the number of children affected by infecto-contagious diseases increases yearly. Some of these diseases are considered to be of risk for hearing.Objective: Check and compare the occurrence of risk indicators of the Hearing Loss during the interval of 10 years in a maternity of São Paulo.Method: Quantitative and retrospective study carried out from the research and review of data of registers supplied by a maternity of the city of São Paulo. We surveyed the registers of babies who were born from January through December of the years of 1995 (n = 2.077) and 2005 (n = 5.129), including those who had risk indicators for deafness and prematurity, low weight and asphyxia, besides having a diagnosis confirmed or suspicion of infecto-contagious diseases of group TORSCH-A.Results: We reviewed reports of 565 children born in 1995, and 1047 born in 2005. Among the risk indicators of deafness, we noticed a significant difference for the indicator of prematurity and asphyxia and there was no significant difference for the low weight indicator. The risk indicators of prematurity, low weight and asphyxia were more frequent than Toxoplasmosis, Syphilis and HIV + . The children born in 1995 tended to have a higher number of risk indicators and/or diseases than those born in 2005 (p < 0.001).Conclusion: The major incidence of indicators in 1995 appoints an improvement to health that diminishes the index of newborns with risk of deafness along 10 years.
Keywords: deafness; disease; newborn